Frame Agreement For Cross-Border Cooperation Between Local Authorities - Kusiak-Winter, Renata (University of Wroclaw. Faculty of Law, Administration & Economics, 2019)
The cross-border cooperation of local authorities, taken up based on the administrative law of each of the states, is marked by both integrating factors that refer to the similarities of the applicable system of law and separating factors arising from the principle of territoriality of administrative law. The frame agreement is a smart solution (a smart tool) of cross-border cooperation, because it enables cooperating territorial self-government units to conduct a unique operation of ‘recompensing’ separating factors with integrating factors.
Keywords: administracja publiczna; samorząd lokalny; władze lokalne; współpraca transgraniczna; porównawcze prawo administracyjne